IMPLEMENTING ABACUS MEDIA TO ENHANCE MATHEMATICS SKILLS AND INTEREST IN FIRST GRADE ELEMENTARY STUDENTS - Samsul Pahmi; Neng Juwita Albela; Najmah Hisan Kamila; Nadiya Hamidah (Jurnal Cakrawala Pendas, 2023)
In an effort to improve students' learning outcomes and enhance the quality of the learning process, it is expected that teachers use enjoyable teaching methods that can increase students' interest in learning. Abacus has been extensively studied as a learning tool for mathematics, but previous researchers have paid insufficient attention to the aspect of differences in basic mathematical abilities and their impact on students' learning outcomes. Therefore, this research is focused on implementing the abacus as a media to improve the interest and mathematical abilities of first-grade elementary school students, particularly in addition and subtraction operations. Data collection was conducted through pre-tests and post-tests, with a sample of 26 students selected based on the diversity of mathematical abilities and gender. Mann-Whitney test was used for data analysis due to the small sample size and the non-normality assumption of the data. The findings indicate that the abacus learning media can significantly improve students' arithmetic abilities, especially for students with low basic arithmetic skills, while high-ability students do not show a significant impact. Furthermore, learning activities using the abacus as a media can also enhance students' independence and interest in learning mathematics, particularly in arithmetic operations. Dalam upaya meningkatkan hasil belajar siswa serta meningkatkan kualitas proses pembelajaran, diharapkan guru menggunakan metode pengajaran yang menyenangkan serta dapat meningkatkan minat belajar siswa. Sempoa telah banyak diteliti sebagai alat pembelajaran untuk matematika, namun peneliti terdahulu masih kurang memberikan perhatian pada aspek perbedaan tingkat kemampuan matematika dasar dan dampaknya terhadap hasil belajar siswa. Oleh karena itu, penelitian ini difokuskan untuk mengimplementasikan media sempoa terhadap peningkatan minat dan kemampuan matematika siswa sekolah dasar tingkat pertama, khususnya pada operasi penjumlahan dan pengurangan. Pengumpulan data dilakukan melalui pre test dan post test, dengan sampel sebanyak 26 siswa yang dipilih berdasarkan keragaman kemampuan matematika dan jenis kelamin. Uji Mann Whitney digunakan untuk analisis data karena ampel termasuk sampel kecil serta tidak memenuhi uji prasyarat normalitas data. Hasil temuan menunjukkan bahwa media pembelajaran sempoa dapat meningkatkan kemampuan berhitung siswa secara signifikan, terutama bagi siswa dengan kemampuan berhitung dasar rendah, sedangkan siswa berkemampuan tinggi tidak memiliki pengaruh yang signifikan. Selain itu, kegiatan pembelajaran dengan menggunakan media sempoa juga dapat meningkatkan kemandirian dan minat siswa dalam belajar matematika khususnya pada operasi hitung.